Factors influencing obesogenic behaviours of adolescent girls and women in low‐ and middle‐income countries: A qualitative evidence synthesis - Trübswasser, Ursula; Verstraeten, Roosmarijn; Salm, Leah; Holdsworth, Michelle; Baye, Kaleab; Booth, Andrew; Feskens, Edith J. M.; Gillespie, Stuart; Talsma, Elise F. (World Obesity Federation, 2021)
This systematic review synthesized the qualitative evidence on factors influencing obesogenic behaviours in adolescent girls and women of reproductive age in low‐ and middle‐income countries (LMICs). This qualitative evidence synthesis followed the framework synthesis approach to extract, analyse and synthesize data. Electronic searches were conducted in the Web of Science, SCOPUS, CABI Abstracts, MEDLINE, PsycINFO and Google Scholar. Studies were eligible if they were conducted in LMICs, of qualitative nature, and reported obesogenic behaviours of female adolescents (10–19 years of age) or women of reproductive age (15–49 years of age). The review resulted in 71 included studies from 27 different countries. Thirty‐two studies focused on dietary behaviours, 17 on physical activity and 22 on both behaviours. Gender norms and failures to recognize the importance of healthy behaviours across the life cycle were important factors. The abundance and promotion of affordable but unhealthy food, food safety concerns, taste preferences and social desirability of foods drive consumption of unhealthy foods. Busy lives and limited exercise spaces keep girls and women from being physically active. Obesogenic behaviours of adolescent girls and women of reproductive age are influenced by factors at individual, social, physical and environmental levels and require diverse solutions to address these factors in LMICs.